Time-Dependent Dynamics Required for the Degradation and Restoration of the Vascular Endothelial Glycocalyx Layer in Lipopolysaccharide-Treated Septic Mice - Shinohara, Akane; Ushiyama, Akira; Iijima, Takehiko (Frontiers in Cardiovascular Medicine, 2021)
The endothelial glycocalyx (GCX) plays a key role in the development of organ failure following sepsis. Researchers have investigated GCX degradation caused by pathological conditions. Nonetheless, the GCX restoration process remains poorly understood. Herein, we developed a model in which GCX restoration could be reproduced in mice using in vivo imaging and a dorsal skinfold chamber (DSC). The severity of sepsis was controlled by adjusting the dose of lipopolysaccharide (LPS) used to trigger GCX degradation in BALB/c mice. We evaluated the GCX thickness, leukocyte-endothelial interactions, and vascular permeability using in vivo imaging through DSC under intravital microscopy. The plasma concentration of syndecan-1(Sdc-1), a GCX structural component, was also determined as a marker of GCX degradation. Thus, we developed a reproducible spontaneous GCX recovery model in mice. Degraded GCX was restored within 24 h by monitoring the serum samples of Sdc-1, the direct visualization of the endothelial GCX thickness, and leukocyte-endothelial interactions. In contrast, indirectly related indicators, such as body weight and blood pressure, required a longer recovery time. This model can be used to study intractable angiopathy following sepsis.